2019
DOI: 10.1177/1533033819852990
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: miR-153-3p Suppresses Inhibitor of Growth Protein 2 Expression to Function as Tumor Suppressor in Acute Lymphoblastic Leukemia

Abstract: Alterations in microRNAs expression can accelerate the development of human cancers. However, the role of miR-153-3p in acute lymphoblastic leukemia remains unknown. The expression of miR-153-3p in acute lymphoblastic leukemia cell lines was measured by quantitative real-time polymerase chain reaction. Effects of miR-153-3p expression on acute lymphoblastic leukemia cell proliferation, migration, and invasion were examined by Cell Counting Kit-8 assay, wound healing assay, and Transwell invasion assay, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…MicroRNAs (miRNAs) are endogenous, small non‐coding RNAs that play an essential role in the regulation of gene expression and tumor progression; in addition, these have been linked to chemotherapy resistance . Many studies have suggested that miR‐153 is a tumor suppressor miRNA . miR‐153‐3p has been reported to suppress the proliferation and invasion of melanoma cells by targeting SNAI1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MicroRNAs (miRNAs) are endogenous, small non‐coding RNAs that play an essential role in the regulation of gene expression and tumor progression; in addition, these have been linked to chemotherapy resistance . Many studies have suggested that miR‐153 is a tumor suppressor miRNA . miR‐153‐3p has been reported to suppress the proliferation and invasion of melanoma cells by targeting SNAI1 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐153 was shown to downregulate Snail expression by directly targeting the 3‐untranslated region of SNAI1. miR‐153‐3p inhibited proliferation, migration, and invasion of acute lymphoblastic leukemia cells by suppressing inhibitor of growth protein 2 expression . In addition to regulating tumor cell infiltration and metastasis, miR‐153‐3p has also been shown to regulate chemosensitivity of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, decreased levels of ING proteins and mRNAs were associated with bad prognosis, in accordance with their tumor suppressor role. Several studies have revealed an endogenous regulation of ING expression by some miRNA such as miR153-3p for ING2 [13]. (Regulation of ING expression by miRNA and other ncRNA is better reviewed in [14]).…”
Section: Introductionmentioning
confidence: 99%